2009
DOI: 10.1007/s11899-009-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of immunoglobulin light chain amyloidosis

Abstract: No therapy is uniformly effective in the management of immunoglobulin light chain amyloidosis (AL amyloidosis). Despite the common generalization, therapy is highly effective. Options available to patients with AL amyloidosis include high-dose therapy, but this is applicable to only about one fourth of patients. Therapies shown to be effective are based on alkylators, dexamethasone, or combinations of an alkylator and steroids. In the past 5 years, novel agents previously shown to be effective in multiple myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…3,27 The combination of melphalan and prednisone had been the mainstay of therapy until a decade or 2 ago, but several therapeutic options have become available in the past 10 to 15 years. 28,29 These include high-dose therapy and SCT, the combination of melphalan and dexamethasone, and more recently the proteasome inhibitor bortezomib and the immunomodulatory drugs thalidomide and lenalidomide used alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…3,27 The combination of melphalan and prednisone had been the mainstay of therapy until a decade or 2 ago, but several therapeutic options have become available in the past 10 to 15 years. 28,29 These include high-dose therapy and SCT, the combination of melphalan and dexamethasone, and more recently the proteasome inhibitor bortezomib and the immunomodulatory drugs thalidomide and lenalidomide used alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…The average treatment related mortality (TRM) in four single center studies is 21% but has been reported as high as 39%[26]. Patients with cardiac involvement and autonomic dysfunction are particularly susceptible to fluid shifts and hypotension as the result of high-dose G-CSF and must be monitored during all phases of treatment including mobilization/collection.…”
Section: Therapeutic Options In Al Amyloidosismentioning
confidence: 99%
“…7,8 Therapy is primarily directed to eradicating the plasma cell clone. [9][10][11][12] Free LC production is frequently observed in plasma cell disorders, including monoclonal gammopathy of undetermined significance, multiple myeloma, and Waldenström macroglobulinemia, but only a fraction of free LC can lose solubility and organize into amyloid deposits. 13 Research has focused on the properties of amyloid-forming LC, and specifically on the variable (V) region, and this for the following reasons: (1) the V region is the amino terminal portion of the Ig LC deputed to antigen binding and responsible for its sequence variation because it is formed via a somatic rearrangement of one of a multitude of germline gene VL segments to one of few joint (J) segments; (2) amyloid deposits are constituted of fragments of LC, comprising the V region and parts of the constant region; and (3) characteristic of AL amyloidosis is the predominance of the isotype over (3:1 ratio), suggesting a genetic propensity in V segments.…”
Section: Introductionmentioning
confidence: 99%